A study on the effect of the addition of copper nanoparticles on the tribological performance of Polyalphaolefin synthetic oil. (2022) - Varalakshmi, M.V.; Venugopal Reddy, V.
Graphical abstract: Abstract: Lubrication has become a powerful tool for minimizing friction and wear between mechanical contact surfaces. In order to improve the lubricating properties of base oil, nanoparticles are added. The present study investigates the effect of the addition of Cu Nanoparticles on the tribological behaviour of Polyalphaolefin (PAO4 ) synthetic oil. Tribo four-ball tester is used to determine the Friction Co-Efficient (COF) for pure PAO4 base oil and also with different concentrations (0.2, 0.4, 0.6, 0.8, 1.0, 1.2, and 1.4 wt%) of Cu nanoparticles. The wear surfaces are examined using a Scanning Electron Microscope (SEM) with Energy Dispersive X-ray Spectroscopy (EDX) and a Tool Makers Microscope. It is observed that Cu nanoparticles, when used as an oil additive, offer excellent anti-friction and anti-wear properties. When 1.0 wt% Cu nanoparticles are added to PAO4 oil, the COF (at the contact point) is lowered by 51.85 percent, and the wear scar diameter is reduced as well when compared to pure PAO4 oil.